PENGARUH PENAMBAHAN GARAM DAN ENZIM TRANSGLUTAMINASE TERHADAP SIFAT FISIK IKAN LUMAT AIR TAWAR - , TRI KUSUMA AGUNG PURUHITA, S.Gz, Dr. Ir. Retno Indrati, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
To anticipate the increased production of freshwater fish by 353% in 2015, research on the development of fresh water fish processing is in urgent needs. In this research, nila fish (Oreochromis niloticus) was used as surimi/mince fish raw materials to replace the over fishing marine fish such as mata goyang fish (Priacrantus macracantus) which have widely used as raw material for surimi/fish mince industry. . Freshwater fish have a low ability to form gels, the important characteristic of good surimi. To improve the physical properties of surimi, a study on the effect of addition of salt and transglutaminase was determined against WHC, hardness, elasticity and gel strength in nila fish mince . Proximate, amino acid composition, and freshness of nila was analysed to determined the quality of raw material. Textur profile analysis (hardness and elasticity), and puncture test (gel strength), SDS PAGE, and microstructure of the fish mince based product of nila were analysed against mata goyang fish as standard. Addition of salt and transglutaminase were varied, i.e 0%